ETNIS CINA DI KESULTANAN SAMBAS TAHUN 1760-1854 - Risa Risa (Khatulistiwa, 2015)
Sultan Umar Akamuddin II (1760-1793) in an effort to increase to income the Sultanate’s Sambas economy, imitated of Mempawah Panembahan to occasion the Ethnic Chinese to work the goldmines.Those efforts have result that marked by increasing the sultanate’s economy. However the policies imposed tight sultan against the Chinese miners and a growing number of ethnic and increasingly established joint venture, the Chinese began to protest by not paying taxes, in violation of the rules of the sultan with the development of agriculture, plantation and trade and control of the Dayak. Therefore, as a last alternative Sultan invited the Dutch to help quell the rebellion Chinese. So, since the moment monopoly and exploitation of mines controlled by the Dutch Colonial, thusending monopoly government trading Sambas Sultanate.